Identification of imaging features that determine quality and repeatability of retinal capillary plexus density measurements in OCT angiography. Issue 4 (16th August 2017) - Fenner, Beau J; Tan, Gavin S W; Tan, Anna C S; Yeo, Ian Y S; Wong, Tien Yin; Cheung, Gemmy C M
Abstract : Purpose: Optical coherence tomography angiography (OCT-A) potentially allows for rapid and non-invasive quantification of retinal capillary plexus density in various disease states. This study aims to identify the key features that influenced the repeatability of OCT-A measurements. Methods: We obtained OCT-A images on two separate visits in 44 healthy eyes from 44 subjects, each imaged with using the Topcon DRI OCT Triton imaging system. The parafoveal vessel density within a 1.5 mm radius centred over the fovea was obtained with the built-in tool for the superficial and deep retinal plexuses. Repeatability of vessel density was determined by intraclass correlation (ICC) and mean variation. We evaluated several image parameters to determine their influence on the repeatability of vessel density measurement in each of the two capillary plexuses. Results: The mean age of the subjects was 70.2±9.2 years, with 64% males. Mean parafoveal vessel density measurements for the first and second visits were 53.3±11.1 and 53.3±10.3 for the superficial plexus and 27.3±8.59 and 27.0±8.78 for the deep plexus. ICC analyses demonstrated that high fine vessel visibility, the absence of motion artefact and software-derived image quality score of 60 or above were necessary to obtain a good (ICC>0.6) or excellent (ICC>0.75) repeatability. Conclusions: Our study identified the imaging parameters that determined the repeatability of quantitative retinal vessel density measurements. These findings have implications in determining if OCT-A images can be used to accurately evaluate serial changes in retinal vessel density.